Individual and Combined Efficacy of Antibiotics and Probiotics on the Growth of Broiler Chicken - Sangeen Khan, Abdul Sattar, Sumaira Salahuddin Lodhi, Azhar Abbas, Farman Ali, Shafiq Ur Rahman, Abbas Ahmad, Muhammad Abbas, Naqeeb Ahmad, Kaleem Ullah, Muhammad Usman Shoukat, Zia Ullah, Muhammad Naveed, Isfahan Tauseef, (Pakistan Journal of Medical & Health Sciences, 2023)
In Pakistan the poultry industry continues to grow to meet the demand for poultry products in world markets therefore, there is need for using probiotics instead of antibiotics to have maximum benefits. The present research work was carried out to study the effect of antibiotic and probiotic in combination and alone on the growth performance of broiler chickens. The effect of antibiotic and probiotic on the body weight gain, feed intake and feed conversion ratio was noted in all the birds. The study was conducted on 300 broilers chickens were divided into 10 groups. Nine of them having 25 birds with the control group having 75 birds. The antibiotic group was named A (A1, A2 and A3). In which A1 was received 150 mg Neomycin/kg feed, A2 was 200mg Neomycin/kg feed and A3 was 250 mg Neomycin/kg respectively. The probiotic group was named “B” and it was further sub divided into B1, B2 and B3. In which B1 was offered 1.5g Protexin/kg feed, B2 was offered 2g Protexin/ kg feed and B3 was 2.5g Protexin/kg feed. The group that received both antibiotic and probiotic was named C and was further divided into C1, C2 and C3. In which C1 was offered 150mg Neomycin and 1.5g Protexin/kg feed, C2 was offered 200 mg Neomycin and 2g Protexin/ kg feed and C3 was offered 250 mg Neomycin and 2.5 g Protexin/kg feed. We concluded that Neomycin antibiotic has not such better effect on the body weight gain, feed intake and feed conversion ratio. Protexin probiotic given alone improves the body weight gain, feed intake and feed conversion ratio. And the best result obtain was that of antibiotic and probiotic given in combination which significantly improves the body weight gain, feed intake and feed conversion ratio.